Graphene–Polyaniline composite based ultra-sensitive electrochemical sensor for non-enzymatic detection of urea. (10th April 2017) - Sha, Rinky; Komori, Kikuo; Badhulika, Sushmee
Graphical abstract: Highlights: Graphene-PANi composite based sensor for non-enzymatic detection of urea. Excellent sensitivity, lower limit of detection, superior reproducibility, selectivity and stability. This novel, low cost sensor is able to predict unknown concentrations of urea in PBS. Validation of sensor through the successful determination of urea in real samples like tap water and milk. Abstract: Detection of urea is of prime importance in food and water safety, dairy industries and environmental monitoring. Traditional methods to detect urea are either expensive and involve sophisticated instrumentation or are based on enzymatic approach of detection. Herein, we report a Graphene-Polyaniline (Gr-PANi) based electrochemical sensor for non-enzymatic detection of urea. Gr-PANi composite was synthesized by electro-deposition of PANi on the surface of Gr modified GCE using cyclic voltammetry (CV) technique. The presence of Gr and PANi in the composite was confirmed using a multitude of characterization techniques which included FESEM, XRD and Raman spectroscopy. The electrochemical behavior of urea at the surface of Gr-PANi modified GCE was studied by CV whereas urea sensing was performed by using simple current-potential (I–V) technique. The current response of the as-fabricated urea sensor was ∼ 4.74 folds greater than that of pure PANi based sensor and ∼ 67.2 times greater than that of pure Gr based sensor. The sensing performance of the composite based urea sensor was optimized by varying the thickness of PANi film. The optimized sensor exhibited lower limit of detection (5.88 μM), excellent reproducibility, selectivity and stability with an enhanced sensitivity of −226.9 μA/μM cm 2 (R 2 = 0.993) in the range of 10 μM–200 μM. The reliability of the as-fabricated sensor was successfully investigated by using it to detect urea concentrations in samples of tap water and milk samples. This highly-sensitive Gr–PANi composite based urea sensor provides a simple, low cost, non-enzymatic approach for detection of urea that find numerous applications in clinical diagnostics, dairy industries, fertilizer plants and environmental monitoring.